2023
DOI: 10.3390/f14020329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Afforestation Years on Soil Properties and Quality

Abstract: As an important means of curbing soil degradation, afforestation has a profound impact on regional soil properties and quality. However, it is still unclear regarding how to conduct a systematic assessment of soil properties and soil quality and the impact of vegetation characteristics and plant functional traits in leguminous plantations with different afforestation years in drylands. Therefore, we investigated the vegetation characteristics and determined the functional traits of leaves and roots and the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In particular, the juvenile plantation, which was only 6 years old at the time of the drought reported in this study, is characterized by an open canopy (Figure 2) and possibly low levels of organic matter in the soil. In fact, afforestation efforts often take several decades to improve various soil properties (Korkanç, 2014; Mongil–Manso et al, 2022; Yao et al, 2023). As a result, the variation in soil moisture observed within the juvenile plantation is most likely caused by the increased physiological water demand of the trees after the drought, as well as differences in forest structure compared to the mature forest.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the juvenile plantation, which was only 6 years old at the time of the drought reported in this study, is characterized by an open canopy (Figure 2) and possibly low levels of organic matter in the soil. In fact, afforestation efforts often take several decades to improve various soil properties (Korkanç, 2014; Mongil–Manso et al, 2022; Yao et al, 2023). As a result, the variation in soil moisture observed within the juvenile plantation is most likely caused by the increased physiological water demand of the trees after the drought, as well as differences in forest structure compared to the mature forest.…”
Section: Discussionmentioning
confidence: 99%
“…Soil BD measurements can enhance our comprehension of soil functions and provide insights into how land use impact soil organic C stocks. A recent study conducted in China showed that as the number of years of afforestation increased, there was a gradual decrease in BD [ 22 ].…”
Section: Introductionmentioning
confidence: 99%